Ulceration of Corticosteroid-Induced StriaeDistensae in Children with Nephrotic Syndrome - Indri Widya Sari; Rusmawardiana; Fifa Argentina (RSUP Dr Moh Hoesin Palembang, 2021)
Striaedistensae(SD) is linear scar tissue in the epidermis and dermis due to excessive stretching of the skin.Striaedistensaeoccurs due to dysfunction of extracellular matrix components that play a role in skin elasticity increasing sensitivity to minor trauma and ulceration. One of the causes is the long-term use of corticosteroids. Systemic corticosteroids are the mainstay of treatment for nephrotic syndrome, so long-term prescribing of corticosteroids should be carried out with caution. It is reported case of a 15-year-old boy with nephrotic syndrome complains of red streaks appearing on his abdomen, back, buttocks, and lower limbs after 2 months of corticosteroid treatment. Pus-filled nodules develop which become ulcers on the red lines of the back. On physical examination found striaedistensae in the abdominal region, posterior trunk, gluteus, femoral and proximal 1/3 bilateral cruris posterior. Found 3 ulcers on the striaedistensae on the posterior trunk, oval to round shape, size 1x1x0,5 cm to 2x1,5x1 cm, base of necrotic tissue, pus contents, wall echoing, edges are not raised, surrounding tissue is erythematous-livid, tenderness, odor, and no induration. On examination of the ulcer swab with Gram stain found Gram-positive bacteria. The culture results showed Staphylococcus aureus. The patient was treated with topical 0.05% retinoic acid every night at SD, and ulcers were treatedsystemic antibiotics of 2 grams ceftriaxone per day for 1 week, as well as ulcer treatment by compressing 1%0 salicylic acid solution, hydrogel, and foam dressing. After 4 weeks of therapy, there was clinical improvement, thinning striae and reduced ulcer size.